2007
DOI: 10.1016/j.physleta.2007.05.074
|View full text |Cite
|
Sign up to set email alerts
|

Quantum pathology of static internal imperfections in flawed quantum computers

Abstract: Even in the absence of external influences the operability of a quantum computer (QC) is not guaranteed because of the effects of residual oneand two-body imperfections. Here we investigate how these internal flaws affect the performance of a quantum controlled-NOT (CNOT) gate in an isolated flawed QC. First we find that the performance of the CNOT gate is considerably better when the two-body imperfections are strong. Secondly, we find that the largest source of error is due to a coherent shift rather than de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 7 publications
(31 citation statements)
references
References 51 publications
2
29
0
Order By: Relevance
“…This prediction is in agreement with that of an approximate master equation [8,9,22,23,24] which has been shown to be quantitatively accurate for a number of systems [8,9].…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…This prediction is in agreement with that of an approximate master equation [8,9,22,23,24] which has been shown to be quantitatively accurate for a number of systems [8,9].…”
Section: Discussionsupporting
confidence: 86%
“…In our recent investigation [8] we showed that internal decoherence, dissipation and coherent shifting, caused by static one and two-body internal imperfections, are potential error sources for flawed QCs [31]. We also showed that a single detector qubit can be configured to probe internal bath dynamics [9] and thus one can obtain valuable information about the bath self-interactions.…”
Section: Test Modelmentioning
confidence: 95%
See 2 more Smart Citations
“…In other configurations, part of a QC can be employed to measure the strength of residual two-body interactions [3], and this knowledge may prove useful for error correction. Idle qubits can also be manipulated to improve performance of the active qubits [4,5]. In fact such self-interacting quantum systems have an exceedingly complex dynamics we are only beginning to explore.…”
Section: Introductionmentioning
confidence: 99%